Editorial (Libellarium: journal for research in the field of information and related sciences, 2014)
This issue of Libellarium features papers based on presentations at the Publishing trends and contexts conference which took place in Pula, Croatia, on December 6-7, 2013 (http://epubconf.sanjamknjige.hr). The conference has gathered a group of experts from prominent European universities in Sweden, Scotland, Lithuania, Poland, Slovenia and Croatia. Together with The e-books research project managed by the Universities of Gothenburg and Borås (http://projectebooks.wordpress.com) and International Book Science Conference organized by Vilnius University, (http://www.ibsc.kf.vu.lt) this new conference reflects both the rising interest in modern publishing in smaller European markets and the reinforcement of ties between the dynamic and progressive publishing industry and the scientific research of its trends and contexts. The two crucial questions were: what is the advantage of publishing in small markets as opposed to big ones, and which successful business models are best suited for small language markets. Most speakers, needless to say, observed these questions in regard to new technologies and phenomena like e-publishing and e-books. The conference, on the one hand, has identified many similarities between small markets, but on the other, showed great differences in the overall acceptance and infrastructural support for e-content development. Among the conclusions based on the presentations and discussions, three are of particular importance. Firstly, small markets have many faces. Markets are shaped by cultural and intellectual heritage, publishing tradition and reading habits, complex political and economic processes, scope, infrastructure, etc. E-books are not intended for ideal, naive readers, but rather for markets which are already influenced by numerous past and present developments. Secondly, a small market is always bilingual, if not multilingual. E-books in national languages, usually distributed via national platforms, are a minority compared to those in English available through global distributors. Finally, although the conference approached the small markets through a comparative perspective, results are not always comparable, since different countries have been covered by different methodologies. Thus, a common instrument, e.g. a questionnaire for all stakeholders in the publishing industry, simultaneously applied in different countries, along with a unique methodology for data collection and analysis, would greatly contribute to a better understanding of publishing practices and book reception in small European markets.